Strategy-proof tie-breaking in matching with priorities - Lars H. Ehlers; Alexander Westkamp (Theoretical Economics, 2018)
A set of indivisible objects is allocated among agents with strict preferences. Each object has a weak priority ranking of the agents. A collection of priority rankings, a priority structure, is solvable if there is a strategy-proof mechanism that is constrained efficient, i.e. that always produces a stable matching that is not Pareto-dominated by another stable matching. We characterize all solvable priority structures satisfying the following two restrictions: (A) Either there are no ties, or there is at least one four-way tie. (B) For any two agents i and j, if there is an object that assigns higher priority to i than j, there is also an object that assigns higher priority to j than i. We show that there are at most three types of solvable priority structures: The strict type, the house allocation with existing tenants (HET) type, where, for each object, there is at most one agent who has strictly higher priority than another agent, and the task allocation with unqualified agents (TAU) type, where, for each object, there is at most one agent who has strictly lower priority than another agent. Out of these three, only HET priority structures are shown to admit a strongly group strategy-proof and constrained efficient mechanism.
Keywords: C78; D61; D78; I20; 330; Weak priorities; stability; constrained efficiency; strategy-proofness